2022
DOI: 10.32598/irj.20.2.910.3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Socio-Demographic Factors of Bipolar Mood Disorders in Children and Adolescents: Identifying the Principal Predictors

Abstract: Objectives: Our objective is to measure the prevalence of bipolar mood disorder (BMD) in Iranian children and adolescents and its comorbidity with psychiatric disorders. Also, the main purpose of this study is to characterize the main risk factors for BMD in children and adolescents. Methods: This is an analytical cross-sectional study. In a community-based study, we sampled 1000 children and adolescents from the age of 6 to 18 years in each province via the multistage cluster sampling method. The total valid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Beginning with the most conservative reports in recent years, studies conducted in Oman and Iran found rates of BD in children and adolescents as low as 0.29% 7 and up to 0.8% 8 and 1% 9 . Earlier research conducted in the United States has reported similar rates between 0.5% (rates of Bipolar I disorder) and 1.0%, and thus at first pass these recent figures seem reassuring and predictably, when bipolar spectrum disorders are included (6.6%) 10 or the illness is subsumed within a broader ‘category’ such as, emotional disorders, its reported prevalence (7.4%) is much higher; 11 underscoring the point that the instrument used to ‘capture’ the disorder is critical in determining its definition.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Beginning with the most conservative reports in recent years, studies conducted in Oman and Iran found rates of BD in children and adolescents as low as 0.29% 7 and up to 0.8% 8 and 1% 9 . Earlier research conducted in the United States has reported similar rates between 0.5% (rates of Bipolar I disorder) and 1.0%, and thus at first pass these recent figures seem reassuring and predictably, when bipolar spectrum disorders are included (6.6%) 10 or the illness is subsumed within a broader ‘category’ such as, emotional disorders, its reported prevalence (7.4%) is much higher; 11 underscoring the point that the instrument used to ‘capture’ the disorder is critical in determining its definition.…”
Section: Introductionmentioning
confidence: 98%
“… The desire for making the diagnosis as early as possible understandable and early diagnosis has been driven by the early intervention movement, which started in schizophrenia/psychosis and has been adopted by those managing mood disorders. However, these paradigms are predicated on significant assumptions, many of which have been challenged 7,27,28 …”
mentioning
confidence: 99%
“…It is difficult for psychiatrists to separate these two patient groups based on clinical observations, at least in the initial interview sessions [8]. The prevalence of bipolar disorder at young ages is low, so this disorder is proposed for children as a secondary diagnosis next to ADHD [9]. A previous study showed that 28.6% of patients with bipolar disorder are misdiagnosed as ADHD [10], [11].…”
Section: Introductionmentioning
confidence: 99%